2005
DOI: 10.1161/01.hyp.0000184251.01159.72
|View full text |Cite
|
Sign up to set email alerts
|

Rat Strain Effects of AT 1 Receptor Activation on D 1 Dopamine Receptors in Immortalized Renal Proximal Tubule Cells

Abstract: Abstract-The dopaminergic and renin-angiotensin systems regulate blood pressure, in part, by affecting sodium transport in renal proximal tubules (RPTs). We have reported that activation of a D 1 -like receptor decreases AT 1 receptor expression in the mouse kidney and in immortalized RPT cells from Wistar-Kyoto (WKY) rats. The current studies were designed to test the hypothesis that activation of the AT 1 receptor can also regulate the D 1 receptor in RPT cells, and this regulation is aberrant in spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
1
24
0
3
Order By: Relevance
“…The decreased power of interaction between D1R and AT1R following short-term exposure to either receptor agonist cannot therefore be explained by a loss of whole cell receptor protein. Previous studies from the group of Felder and Jose (21) has shown that long-term, generally 24-h, exposure to D1R or AT1R agonists decreases the total abundance of the reciprocal receptor (21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The decreased power of interaction between D1R and AT1R following short-term exposure to either receptor agonist cannot therefore be explained by a loss of whole cell receptor protein. Previous studies from the group of Felder and Jose (21) has shown that long-term, generally 24-h, exposure to D1R or AT1R agonists decreases the total abundance of the reciprocal receptor (21).…”
Section: Discussionmentioning
confidence: 95%
“…Long-term dopamine exposure is known to decrease AT 1 receptors (AT1R) in renal proximal tubular cells (7). Furthermore, studies by Zeng et al (21) have shown that long-term stimulation of AT1R results in an upregulation of D1-like receptors (D1R). This effect was not observed in spontaneously hypertensive rats, indicating that the interaction between AT1R and D1R has an impact on blood pressure regulation.…”
mentioning
confidence: 99%
“…5,6 We hypothesize that D 1 , D 3 , D 4 , and D 5 receptors interact (in RPTs or elsewhere in the nephron) among or between themselves, and/or other GPCRs, such as angiotensin and endothelin receptors, to regulate sodium excretion. 6,7,12,24,32,40,41,55,56 The ultimate effect of dopamine is the sum of the interactions of those dopamine receptor subtypes and other GPCRs that may depend on the state of sodium balance. These interactions are impaired in SHRs.…”
Section: Zeng Et Al D 3 Receptor Regulation Of D 1 Receptor In Kidneymentioning
confidence: 99%
“…[1][2][3] Several lines of evidence suggest that AT1R and D1R form a heteromeric signaling complex. [4][5][6] We recently reported that activation of either AT1R or D1R might cause internalization and/or interruption of the signaling capacity of the other receptor. 6 These observations imply that AT1R and D1R may allosterically modulate each other.…”
Section: Introductionmentioning
confidence: 99%